Implikasi Yuridis Penerapan Perkara Koneksitas dalam Tindak Pidana Korupsi berdasarkan Undang-Undang KPK - Muh. Fahmi Ramadhani; Amirrudin Hanafi; Vivi Nur Qalbi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to examine the legal implications of implementing the concept of connected criminal cases (koneksitas) in corruption offenses as regulated under Article 42 of Law Number 30 of 2002 concerning the Corruption Eradication Commission, as amended by Law Number 19 of 2019, in relation to the Constitutional Court Decision Number 87/PUU-XXI/2023. Connected criminal cases involve offenders subject to both general and military jurisdictions, creating legal issues regarding the determination of the competent judicial institution to examine and adjudicate such cases. This research employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary legal sources, including legislation and court decisions, as well as secondary legal sources, such as books, journals, and other relevant legal literature. The findings indicate that Article 42 of the KPK Law grants the Corruption Eradication Commission (KPK) the authority to handle connected criminal cases, provided that the law enforcement process is initiated by the KPK, as reaffirmed by Constitutional Court Decision Number 87/PUU-XXI/2023. Nevertheless, overlapping authority between the KPK and military courts continues to create jurisdictional conflicts in practice. Furthermore, connected criminal cases are more frequently resolved through case splitting (splitsing) rather than joint investigation teams, potentially leading to inconsistent judicial decisions. The study concludes that the implementation of connected criminal cases in corruption offenses still faces legal challenges due to regulatory disharmony and weak institutional coordination, highlighting the need for clear technical guidelines to ensure legal certainty and effective corruption eradication